KONTRADIKSI ANTARA MAMAK DENGAN KEMANAAN DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR PROVINSI RIAU - Widarto, Hendra; Tantoro, Swiss (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to look at, how should puncture Mamak against Kemanakan in Tanjung Village community, and to see what factors caused the Contradiction Between Mamak With the nephew. To analyze the data of this study is done qualitatively, data collected later in the mentioned descriptively that depicts or communicating the results of research with a description of logical sentences that can be understood and easy to understand. This research was conducted in the village of Tanjung Hulu subdistrict Koto Kampar Kampar regency. 8 (eight) informans, 4 status as mamak and 4 as kemakan. The results of this study show the contradictions and changes Sosil Between Mamak With a nephew in various fields such as economics, education, inheritance, and of marriage. This occurs by some cause them. In Education: Mamak no longer determines nephew education, because mamak not want to help the nephew of both enlightening and deri financing. In the economic field: the limited scope for a Mamak in the economy, thus making the Mamak forget nephew. In the field of heritage treasures: Mamak error in using the treasures, thus making the nephew does not want to trust mamak. In the field of marriage:Keywords: Contradictions and Social Change.